TosR-Mediated Regulation of Adhesins and Biofilm Formation in Uropathogenic Escherichia coli - Courtney L. Luterbach (American Society for Microbiology, 2018)
ABSTRACT Uropathogenic Escherichia coli strains utilize a variety of adherence factors that assist in colonization of the host urinary tract. TosA (type one secretion A) is a nonfimbrial adhesin that is predominately expressed during murine urinary tract infection (UTI), binds to kidney epithelial cells, and promotes survival during invasive infections. The tosRCBDAEF operon encodes the secretory machinery necessary for TosA localization to the E. coli cell surface, as well as the transcriptional regulator TosR. TosR binds upstream of the tos operon and in a concentration-dependent manner either induces or represses tosA expression. TosR is a member of the PapB family of fimbrial regulators that can participate in cross talk between fimbrial operons. TosR also binds upstream of the pap operon and suppresses PapA production. However, the scope of TosR-mediated cross talk is understudied and may be underestimated. To quantify the global effects of TosR-mediated regulation on the E. coli CFT073 genome, we induced expression of tosR, collected mRNA, and performed high-throughput RNA sequencing (RNA-Seq). These findings show that production of TosR affected the expression of genes involved with adhesins, including P, F1C, and Auf fimbriae, nitrate-nitrite transport, microcin secretion, and biofilm formation. IMPORTANCE Uropathogenic E. coli strains cause the majority of UTIs, which are the second most common bacterial infection in humans. During a UTI, bacteria adhere to cells within the urinary tract, using a number of different fimbrial and nonfimbrial adhesins. Biofilms can also develop on the surfaces of catheters, resulting in complications such as blockage. In this work, we further characterized the regulator TosR, which links both adhesin production and biofilm formation and likely plays a crucial function during UTI and disseminated infection.